Intraoperative ketamine may increase risk of post-operative delirium after complex spinal fusion for adult deformity correction - Elsamadicy, Aladine A. (J Spine Surg, 2019)
BACKGROUND: For complex surgery, intraoperative ketamine administration is readily used to reduce post-operative pain. However, there have been a few studies suggesting that intraoperative ketamine may have deleterious effects and impact post-operative delirium. Therefore, we sought to identify the impact that intraoperative ketamine has on post-operative outcomes after complex spinal surgery involving ≥5 level fusions. METHODS: The medical records of 138 adult (≥18 years old) spine deformity patients undergoing elective, primary complex spinal fusion (≥5 level) for deformity correction at a major academic institution from 2010 to 2015 were reviewed. We identified 98 (71.0%) who had intraoperative ketamine administration and 40 (29%) who did not (Ketamine-Use: n=98; No-Ketamine: n=40). Patient demographics, comorbidities, intra- and post-operative complication rates were collected for each patient. The primary outcome investigated in this study was the rate of post-operative delirium. A multivariate nominal-logistic regression analysis was used to determine the independent association between intraoperative ketamine and post-operative delirium. RESULTS: Patient demographics and comorbidities were similar between both cohorts, including age, gender, and BMI. The median number of fusion levels operated, length of surgery, estimated blood loss, and proportion of patients requiring blood transfusions were similar between both cohorts. Postoperative complication profile was similar between the cohorts, except for the Ketamine-Use cohort having significantly higher proportion of patients experiencing delirium (Ketamine-Use: 14.3% vs. No-Ketamine: 2.6%, P=0.047). In a multivariate nominal-logistic regression analysis, intraoperative Ketamine-Use was independently associated with post-operative delirium (OR: 9.475, 95% CI: 1.026–87.508, P=0.047). CONCLUSIONS: Our study suggests that the intraoperative use of ketamine may increase the risk of post-operative delirium. Further studies are necessary to understand the physiological effect intraoperative ketamine has on patients undergoing complex spinal fusions in order to better overall patient care and reduce healthcare resources.